Public Relations Strategy in Increasing Brand Awareness of Boarding-Based School - Rofiki, Moh.; Nurjannah, Uus Devi (Electronic Journal of Education, Social Economics and Technology, 2024)
In the increasingly competitive era of education globalization, brand awareness is one of the most important aspects to strengthen the prestige and positive image of an educational institution. This study aims to analyze public relations strategies for increasing brand awareness as well as the supporting and inhibiting factors at Insan Terpadu Junior High School, a dormitory-based school known for its slogan Qur'anic Character, Future Insight. The research approach used qualitative case studies. Data were obtained by participant observation and in-depth interviews with the principal, head of public relations, head of student affairs, teachers, and students. The results showed that the public relations strategies used include active communication with student guardians through social media, innovative programs such as English Peer Tutoring (EPT), and religious-based activities such as Rihlatut Tasmi's Wa Khotmil Qur'an. The main supporting factors are the involvement of student guardians and the utilization of social media, while constraints include limited human resources and budget. The importance of a comprehensive public relations strategy to build positive relationships with the public and increase the competitiveness of the institution so that it will have an impact on increasing the reputation and public trust in Insan Terpadu Junior High School, which in turn strengthens the school's brand awareness and attracts more potential students.